The use of pollen morphology to disentangle the origin, early evolution, and diversification of the asteraceae - Tellería, María Cristina; Barreda, Viviana Dora; Jardine, Phillip E.; Palazzesi, Luis (International Journal of Plant Sciences)
Pollen morphology has proven to be particularly informative for elucidating the evolutionary relationships within Asteraceae (or Compositae). However, very few studies have attempted to reconstruct the character states across the family based on pollen data. Here, we mapped pollen characters onto a recent phylogenomic tree of Asteraceae based on new and published observations. We also revised the pollen morphology of selected lineages of the family largely distributed in South America, including living representatives of the oldest fossils of Asteraceae. By mapping the three selected pollen characters onto a recent phylogenomic framework, we detected shifts and trends across the evolution of the family. Our study showedthat Asteraceae pollen grains ancestrally possessed microspines and a non-layered ecaveate exine. The morphology of this reconstructed ancestor agrees with that of the oldest extinct fossil pollen grains assigned to Barnadesieae discovered in late Cretaceous sediments from Antarctica and New Zealand. The presence of a layered sexine with stout columellae characterizes the most recent common ancestor of all Asteraceae, except for the sister clade Barnadesieae. This extinct ancestor also appears to be represented in the fossil record with morphologically related species of Mutisiapollis, distributed in Paleogene sediments across Patagonia, Africa and Australia. Taken together, our work supports previous studies indicatingthat the range of variation in pollen morphology across Asteraceae is wide, yet phylogenetically structured. However, pollen characters (and character states) fail to support the unequivocal recognition of the selected monophyletic South American groups. Although preliminary, our results highlight the importance of scoring pollen characters to identify fossil specimens, explore character evolution and reconstruct ancestral forms. Fil: Tellería, María Cristina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. ...